Assessment of Knowledge, Attitude and Practice Regarding Blood Donation among Paramedical Personnel in a Teaching Hospital, Hassan, Karnataka (Indian Journal of Public Health Research & Development, 2021)
Background: Voluntary, non - remunerated blood donation is the foundation for safe and sustainable bloodsupply. Health care providers, especially non physician personnel or paramedical personnel, play an importantrole in motivating and promoting blood donation as they come more in contact with public as representativesof the health system and hence need to possess a comprehensive and accurate knowledge regarding blooddonation. Methodology: A Cross–sectional study was conducted to assess the knowledge of blood donationamong 285 paramedical personnel working in Hassan institute of medical sciences, Karnataka which isa tertiary care teaching hospital. A pretested Questionnaire regarding blood donation KAP (knowledge,attitude and practice) were administered to all the paramedical personnel who consented to take part in thestudy after adequate sample size estimation. Results: More than 90% of staff had good knowledge regardingthe blood groups and the eligibility criteria. 253 (88.8%) respondents considered blood donation as good and205(71.9%) believed it was safe to donate blood but in practice only 116(40.7%) had ever donated blood.Male workers were more likely to donate blood (p
Keywords: Voluntary blood donation, paramedical personnel, awareness